Carrier for electrostatic charge image development, electrostatic charge image developer, process cartridge, image forming apparatus, and image forming method

JP2025026177APending Publication Date: 2025-02-21FUJIFILM BUSINESS INNOVATION CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023131600
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-10
Publication Date
2025-02-21

AI Technical Summary

Benefits of technology

【0007】 <1>に係る発明によれば、磁性粒子の内部空隙に無機粒子が含有されない場合に比べ、高温高湿環境下において交流電圧を印加する現像方式で形成した画像の濃度ムラが抑制される静電荷像現像用キャリアが提供される。 <2>に係る発明によれば、磁性粒子の内部空隙率が2%未満又は10%超えである場合に比べ、高温高湿環境下において交流電圧を印加する現像方式で形成した画像の濃度ムラが抑制される静電荷像現像用キャリアが提供される。 <3>に係る発明によれば、樹脂組成物の断面において樹脂の合計面積に対する無機粒子の合計面積の比率が0.02未満又は0.10超えである場合に比べ、高温高湿環境下において交流電圧を印加する現像方式で形成した画像の濃度ムラが抑制される静電荷像現像用キャリアが提供される。 <4>に係る発明によれば、樹脂組成物の断面において無機粒子の合計面積に対する導電性粒子の合計面積の比率が0.005超えである場合に比べ、高温高湿環境下において交流電圧を印加する現像方式で形成した画像の濃度ムラが抑制される静電荷像現像用キャリアが提供される。 <5>に係る発明によれば、無機粒子の個数平均粒径が5nm未満又は90nm超えである場合に比べ、高温高湿環境下において交流電圧を印加する現像方式で形成した画像の濃度ムラが抑制される静電荷像現像用キャリアが提供される。 <6>に係る発明によれば、樹脂が窒素原子を有する樹脂を含まない場合に比べ、高温高湿環境下において交流電圧を印加する現像方式で形成した画像の濃度ムラが抑制される静電荷像現像用キャリアが提供される。 <7>に係る発明によれば、樹脂が窒素原子を有する樹脂からなる場合に比べ、画像濃度の環境差が抑制される静電荷像現像用キャリアが提供される。 <8>、<9>、<10>、又は<11>に係る発明によれば、磁性粒子の内部空隙に無機粒子が含有されない静電荷像現像用キャリアを適用した場合に比べ、高温高湿環境下において交流電圧を印加する現像方式で形成した画像の濃度ムラが抑制される静電荷像現像剤、プロセスカートリッジ、画像形成装置、又は画像形成方法が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026177000002
    Figure 2025026177000002
  • Figure 2025026177000003
    Figure 2025026177000003
  • Figure 2025026177000004
    Figure 2025026177000004
Patent Text Reader

Abstract

To provide a carrier for electrostatic charge image development that can prevent density unevenness of an image formed by a developing method for applying an AC voltage in a high temperature and high humidity environment.SOLUTION: A carrier for electrostatic charge image development has: a magnetic particle having an internal gap; and a resin composition arranged in at least part of the internal gap, and containing a resin and inorganic particles including at least one kind selected from a group consisting of silica, alumina, and calcium carbonate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrostatic image developing carrier, an electrostatic image developer, a process cartridge, an image forming apparatus, and an image forming method. [Background technology]

[0002] Patent Document 1 describes a composite material made of ferrite particles, having a specific pore volume, an average internal void area in a specific range, and a void area of ​​20 μm 2 The above-mentioned carrier for electrophotographic development is disclosed in which the surface of a carrier core material having an internal void ratio of 1.8% or less is coated with a resin.

[0003] Patent Document 2 discloses a carrier for developing electrostatic images, which has a core material and a coating resin layer that contains nitrogen-containing resin particles and inorganic oxide particles and coats the core material, and the surface exposure rate of the nitrogen-containing resin particles is 0.8% or more and 3.0% or less. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-061188 A [Patent Document 2] Patent Publication No. 2021-051216 Summary of the Invention [Problem to be solved by the invention]

[0005] The object of the present invention is to provide a carrier for developing electrostatic images which suppresses uneven density in images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, compared to a case in which inorganic particles are not contained in the internal voids of magnetic particles. [Means for solving the problem]

[0006] Means for solving the above problems include the following aspects. <1> Magnetic particles having internal voids; a resin composition that is disposed in at least a portion of the internal voids and contains inorganic particles including at least one selected from the group consisting of silica, alumina, and calcium carbonate, and a resin; A carrier for developing electrostatic images comprising: <2> The internal porosity of the magnetic particles is 2% or more and 10% or less. <1> 2. The electrostatic image developing carrier according to claim 1 . <3> In a cross section of the resin composition, the ratio of the total area of ​​the inorganic particles to the total area of ​​the resin is 0.02 or more and 0.10 or less. <1> or <2> 2. The electrostatic image developing carrier according to claim 1 . <4> The resin composition does not contain conductive particles, or contains the conductive particles, and a ratio of a total area of ​​the conductive particles to a total area of ​​the inorganic particles in a cross section of the resin composition is 0.005 or less. <1> ~ <3> 10. The electrostatic image developing carrier according to claim 9, <5> The number average particle size of the inorganic particles is 5 nm or more and 90 nm or less. <1> ~ <4> 10. The electrostatic image developing carrier according to claim 9, <6> The resin includes a resin having a nitrogen atom. <1> ~ <5> 10. The electrostatic image developing carrier according to claim 9, <7> The resin further includes a resin having no nitrogen atoms. <6> 2. The electrostatic image developing carrier according to claim 1 . <8> a toner for developing an electrostatic image; <1> ~ <7> 10. The electrostatic image developing carrier according to claim 9, 13. An electrostatic image developer comprising: <9> <8> and a developing device that contains the electrostatic image developer according to claim 1 and develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus. <10> An image carrier; a charging device for charging the surface of the image carrier; an electrostatic image forming device for forming an electrostatic image on the charged surface of the image carrier; <8> a developing device that contains the electrostatic image developer according to claim 1 and develops the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer; a transfer device for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing device for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising: <11> a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; <8> a developing step of developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer according to claim 1; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1, Effect of the Invention

[0007] <1> According to the present invention, there is provided a carrier for developing electrostatic images which suppresses uneven density in images formed using a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, compared to when inorganic particles are not contained in the internal voids of magnetic particles. <2> According to the present invention, there is provided a carrier for developing electrostatic images which suppresses uneven density in images formed using a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, compared to when the internal porosity of the magnetic particles is less than 2% or exceeds 10%. <3> According to the present invention, there is provided a carrier for developing electrostatic images, which suppresses uneven density in images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, compared to when the ratio of the total area of ​​the inorganic particles to the total area of ​​the resin in the cross section of the resin composition is less than 0.02 or exceeds 0.10. <4> According to the present invention, there is provided a carrier for developing electrostatic images in which density unevenness in an image formed by a development method in which an AC voltage is applied in a high-temperature and high-humidity environment is suppressed, as compared with a case in which the ratio of the total area of ​​conductive particles to the total area of ​​inorganic particles in the cross section of the resin composition exceeds 0.005. <5> According to the present invention, there is provided a carrier for developing electrostatic images which suppresses uneven density in images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, compared to when the number-average particle size of the inorganic particles is less than 5 nm or exceeds 90 nm. <6> According to the present invention, there is provided a carrier for developing electrostatic images which suppresses uneven density in images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, compared to a case in which the resin does not contain a resin having a nitrogen atom. <7> According to the present invention, there is provided a carrier for developing electrostatic images in which the environmental difference in image density is suppressed, as compared with the case where the resin is made of a resin having a nitrogen atom. <8> , <9> , <10> or <11> According to the invention, there is provided an electrostatic image developer, process cartridge, image forming apparatus, or image forming method which suppresses uneven density of an image formed by a development method in which an AC voltage is applied in a high temperature and high humidity environment, compared to the case where an electrostatic image developing carrier is used that does not contain inorganic particles in the internal voids of magnetic particles. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic diagram for explaining a method for confirming internal voids in magnetic particles. [Diagram 2] 1 is a schematic configuration diagram illustrating an example of an image forming apparatus according to an embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram illustrating an example of a process cartridge that is detachably mounted to the image forming apparatus according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.

[0010] In the present disclosure, a numerical range indicated using "~" indicates a range that includes the numerical values ​​before and after "~" as the minimum and maximum values, respectively.

[0011] In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0012] In the present disclosure, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.

[0013] When an embodiment of the present disclosure is described with reference to the drawings, the configuration of the embodiment is not limited to the configuration shown in the drawings. In addition, the size of the members in each drawing is conceptual, and the relative relationship between the sizes of the members is not limited to this.

[0014] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified.

[0015] In the present disclosure, the particles corresponding to each component may include multiple types. When multiple types of particles corresponding to each component are present in the composition, the particle size of each component means the value for a mixture of the multiple types of particles present in the composition, unless otherwise specified.

[0016] In the present disclosure, "(meth)acrylic" means at least one of acrylic and methacrylic, and "(meth)acrylate" means at least one of acrylate and methacrylate.

[0017] In this disclosure, "toner for developing electrostatic images" is also referred to as "toner", "carrier for developing electrostatic images" is also referred to as "carrier", and "electrostatic image developer" is also referred to as "developer".

[0018] [Electrostatic image developing carrier] The carrier for developing electrostatic images according to the present embodiment includes magnetic particles having internal voids, and a resin composition that is disposed in at least a part of the internal voids and contains inorganic particles including at least one selected from the group consisting of silica, alumina, and calcium carbonate, and a resin. The carrier according to the present embodiment may further include a resin coating layer that coats the magnetic particles, if necessary. Hereinafter, at least one selected from the group consisting of silica, alumina, and calcium carbonate will also be referred to as "specific inorganic particles", and a resin composition containing specific inorganic particles and a resin will also be referred to as "specific resin composition".

[0019] In this embodiment, the specific resin composition is disposed in the internal voids of the magnetic particles, thereby suppressing uneven density of images formed by a development method in which an AC voltage is applied in a high-temperature and high-humidity environment. The reason for this is unclear, but is presumed to be as follows.

[0020] One of the causes of density unevenness in images formed by a development method that applies an AC voltage is poor responsiveness of the carrier to the AC voltage. In particular, it is considered that the higher the dielectric constant of the carrier as a whole, the more likely it is that the response to the AC voltage is delayed in a high-temperature and high-humidity environment, and the more likely image unevenness is to occur. Another cause of uneven density in an image formed using a development method that applies an AC voltage is cracks, chips, etc. in the magnetic particles that are the core material of the carrier. Cracks and chips in the magnetic particles are caused, for example, by mechanical loads imposed by stirring in a development device. It is believed that cracks, chips, etc. in the magnetic particles cause changes in the chargeability of a portion of the carrier, resulting in areas of different density in the formed image and causing image unevenness.

[0021] In contrast, in this embodiment, a specific resin composition containing specific inorganic particles is arranged in the internal voids of the magnetic particles. Since the specific inorganic particles have a low relative dielectric constant, it is believed that the presence of the specific inorganic particles in the internal voids of the magnetic particles reduces the dielectric constant of the carrier as a whole, improving the responsiveness to AC voltage. It is also presumed that the improved responsiveness to AC voltage results in small voltage fluctuations, nearly uniform toner placement, and suppressed density unevenness, even when a solid image is formed in a high-temperature, high-humidity environment. In addition, it is believed that the presence of resin in the internal voids of the magnetic particles reduces mechanical loads due to the elasticity of the resin, thereby suppressing cracking and chipping of the magnetic particles, which is in turn believed to suppress the occurrence of image unevenness caused by cracking, chipping, etc. of the magnetic particles.

[0022] For the above reasons, it is presumed that in this embodiment, density unevenness in an image formed by a development method in which an AC voltage is applied in a high-temperature and high-humidity environment is suppressed. The carrier according to this embodiment will be described in detail below.

[0023] <Magnetic particles> There are no limitations on the magnetic particles as long as they are magnetic particles having internal voids. Specific examples of the magnetic particles include particles of magnetic oxides such as ferrite, magnetite, etc. The magnetic particles are preferably particles of magnetic oxides, and more preferably ferrite particles.

[0024] From the viewpoint of suppressing image unevenness, the internal porosity of the magnetic particles is preferably from 2% to 10%, more preferably from 2% to 8%, and even more preferably from 3% to 6%. By making the internal void ratio of the magnetic particles equal to or greater than the lower limit, the specific inorganic particles are likely to be present in the internal voids of the magnetic particles, and the dielectric constant of the carrier as a whole is likely to be low. This is believed to improve the responsiveness to AC voltage and suppress the occurrence of density unevenness in images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment. Furthermore, by keeping the internal porosity of the magnetic particles at or below the upper limit, the magnetic particles are less likely to crack or chip due to mechanical load, and it is believed that the occurrence of image unevenness resulting therefrom is suppressed. When the magnetic particles are ferrite particles, the internal porosity of the magnetic particles can be adjusted to the above range by controlling the oxygen concentration and the firing temperature during firing. Specifically, the internal porosity can be increased by increasing the oxygen concentration or decreasing the firing temperature.

[0025] Whether or not the magnetic particles have internal voids and the internal void ratio of the magnetic particles are confirmed as follows. First, the carrier is embedded in an embedding agent such as epoxy resin to obtain an embedded product, and then the surface of the embedded product is cut with a diamond knife or the like. The cutting is continued until a sufficient cross section of the magnetic particles is secured to obtain a measurement sample, and the cross section is photographed. The cross section may be photographed by a conventionally known method such as a scanning electron microscope (SEM). Next, a cross section of one magnetic particle is analyzed using a conventionally known image analysis software (for example, WinRoof (Mitani Corporation)). Specifically, as shown in Fig. 1, a gap (i.e., a space where no magnetic particle components exist) present in a square 220 having two opposing vertices, 218a and 218b, which are 3 / 4 of the radius from the center 216 of the circumscribing circle 212 on one diameter 214 of the circumscribing circle 212 of the particle in the cross section 210 of the magnetic particle, is confirmed.

[0026] Whether or not the magnetic particles have internal voids is confirmed by analyzing the cross sections of 100 magnetic particles and confirming whether or not voids exist within the squares 220. In the SEM image of the cross section of the magnetic particle, the voids appear as black regions. When it is confirmed that voids exist within the squares 220 in the cross sections of 90 or more magnetic particles, the magnetic particles are deemed to have internal voids. The internal porosity (%) of a magnetic particle is calculated using the following formula: In the formula, SH is the total area of ​​voids present in the square 220 of 100 magnetic particles, and ST is the total area of ​​the square 220 of 100 magnetic particles. Formula: Internal porosity (%)=(SH / ST)×100 The diameter 214 at any position of the circumscribing circle 212 of the magnetic particle is selected on the cross section 210 of the magnetic particle. The cross section 210 of the magnetic particle to be measured is preferably a cross section cut near the center of the magnetic particle.

[0027] The number-average particle diameter of the magnetic particles is preferably 15 μm or more and 100 μm or less, more preferably 20 μm or more and 80 μm or less, and even more preferably 30 μm or more and 60 μm or less, from the viewpoints of obtaining an appropriate adhesive force between the toner and the carrier, obtaining a sufficient amount of toner development, and obtaining an appropriate magnetic brush and forming an image with excellent fine line reproducibility. The number-average particle size of the magnetic particles is determined by analyzing the cross sections of 100 magnetic particles in the same manner as in the above-mentioned method for confirming internal voids in the magnetic particles. Specifically, the circle-equivalent diameter of the cross section 210 of each particle is determined, and the average value for the 100 particles is taken as the number-average particle size of the magnetic particles.

[0028] The magnetic force of the magnetic particles is preferably 50 emu / g or more, more preferably 60 emu / g or more, in terms of saturation magnetization in a magnetic field of 3000 oersteds. The saturation magnetization is measured using a vibrating sample magnetic measuring device VSMP10-15 (manufactured by Toei Kogyo Co., Ltd.). The measurement sample is packed in a cell with an inner diameter of 7 mm and a height of 5 mm and set in the device. The measurement is performed by applying a magnetic field and sweeping up to a maximum of 3000 oersteds. The applied magnetic field is then reduced, and a hysteresis curve is prepared on a recording paper. The saturation magnetization, residual magnetization, and retentivity are determined from the curve data.

[0029] The volume resistivity of magnetic particles is 1×10 5 Ω cm or more 1×10 9 Ω cm or less is preferable, and 1×10 7 Ω cm or more 1×10 9 Ω·cm or less is more preferable. The volume resistivity (Ω·cm) of magnetic particles is measured as follows: 2 The object to be measured is placed flat on the surface of the circular jig on which the electrode plate is arranged, with a thickness of 1 mm to 3 mm, to form a layer. 2 The layer is sandwiched between two electrode plates. In order to eliminate any gaps between the objects being measured, a 4 kg load is placed on the electrode plates placed on the layer, and then the layer thickness (cm) is measured. Both electrodes above and below the layer are connected to an electrometer and a high-voltage power supply generator. A high voltage is applied to both electrodes so that the electric field is 103.8 V / cm, and the current value (A) that flows at this time is read. The measurement environment is a temperature of 20°C and a relative humidity of 50%. The formula for calculating the volumetric electrical resistivity (Ω·cm) of the object being measured is as shown below. R=E×20 / (I-I0) / L In the above formula, R is the volume resistivity (Ω cm) of the object to be measured, E is the applied voltage (V), I is the current value (A), I0 is the current value (A) at an applied voltage of 0 V, and L is the layer thickness (cm). The coefficient 20 is the area of ​​the electrode plate (cm 2 )

[0030] <Specific resin composition> The specific resin composition is disposed in at least a part of the internal voids of the magnetic particles. The magnetic particles need only have internal voids in which the specific resin composition is disposed, and may further have internal voids in which the specific resin composition is not disposed. Examples of internal voids in which the specific resin composition is not disposed include internal voids in which only the resin is disposed, internal voids in which only the specific inorganic particles are disposed, and internal voids in which neither the resin nor the specific inorganic particles are disposed. Confirmation that the specific resin composition is disposed in the internal voids of the magnetic particles is performed by observing and analyzing the cross section of the magnetic particles in the same manner as the above-mentioned method for confirming the internal voids in the magnetic particles. For example, when the specific inorganic particles are silica, elemental analysis is performed on the cross section of the internal voids of the magnetic particles by energy dispersive X-ray spectroscopy (EDX), and the area where silica is present is confirmed by mapping the area where silicon is present, and the area where resin is present is confirmed by mapping the area where carbon is present. Note that when the specific inorganic particles are alumina, the area where aluminum element is present is confirmed by mapping, and when the specific inorganic particles are calcium carbonate, the area where calcium element is present is confirmed by mapping. The specific resin composition contains at least the specific inorganic particles and a resin, and may further contain other components.

[0031] (Specified inorganic particles) The specific inorganic particles contained in the specific resin composition are at least one selected from the group consisting of silica, alumina, and calcium carbonate. The specific inorganic particles may be composed of only one type of inorganic particles, or may be composed of two or more types of inorganic particles. Among these, the specific inorganic particles preferably contain silica from the viewpoint of reducing the dielectric constant of the carrier as a whole and suppressing uneven concentration.

[0032] The surface of the specific inorganic particles may be subjected to hydrophobic treatment. When the specific inorganic particles contain silica, examples of the hydrophobic treatment agent include known organosilicon compounds having an alkyl group (e.g., methyl group, ethyl group, propyl group, butyl group, etc.), and specific examples include alkoxysilane compounds, siloxane compounds, and silazane compounds. Among these, the hydrophobic treatment agent is preferably a silazane compound, and hexamethyldisilazane is preferred. The hydrophobic treatment agent may be used alone or in combination of two or more kinds. By carrying out the hydrophobic treatment, the inorganic particles are easily dispersed uniformly in the resin composition, and the dielectric constant of the carrier as a whole is reduced, thereby suppressing unevenness in concentration.

[0033] Examples of methods for hydrophobizing specific inorganic particles with a hydrophobizing agent include a method in which supercritical carbon dioxide is used to dissolve the hydrophobizing agent in supercritical carbon dioxide and adhere the hydrophobizing agent to the surfaces of the specific inorganic particles; a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is applied (e.g., sprayed or coated) to the surfaces of specific inorganic particles in the atmosphere to adhere the hydrophobizing agent to the surfaces of specific inorganic particles; and a method in which a solution containing a hydrophobizing agent and a solvent that dissolves the hydrophobizing agent is added to a specific inorganic particle dispersion in the atmosphere, the solution is maintained, and then the mixed solution of the specific inorganic particle dispersion and the solution is dried.

[0034] From the viewpoint of suppressing unevenness in density, the number average particle size of the specific inorganic particles is preferably 5 nm or more and 90 nm or less, more preferably 5 nm or more and 50 nm or less, and even more preferably 7 nm or more and 50 nm or less. By having the number-average particle size of the specific inorganic particles within the above range, the magnetic particles are less likely to crack, chip, etc. due to mechanical load compared to when the particle size is larger or smaller than the above range, and it is believed that the occurrence of image unevenness resulting from this is suppressed. The number-average particle size of the specific inorganic particles is determined by analyzing the cross section of the magnetic particles in the same manner as the above-mentioned method for confirming the internal voids in the magnetic particles. Specifically, the number-average particle size of the specific inorganic particles is determined by calculating the circle-equivalent diameter of each of 100 specific inorganic particles present in the internal voids of the magnetic particles and averaging the circle-equivalent diameters of each particle. Preferably, the observation and analysis are performed using a field emission scanning electron microscope (FE-SEM) capable of high-resolution imaging. Specific examples of FE-SEM include Hitachi High-Tech's Regulus series "SU8010", "Regulus8100", "Regulus8220", "Regulus8230", "Regulus8240", and "ULTRA55", and JEOL's "JSM-IT800". The number average particle size of the inorganic particles contained in the specific resin composition and the resin coating layer may be the number average particle size of the inorganic particles measured with a laser diffraction / scattering type particle size distribution measuring device.

[0035] The amount of the specific inorganic particles contained in the specific resin composition is preferably an amount such that the ratio of the total area of ​​the specific inorganic particles to the total area of ​​the resin in the cross section of the specific resin composition is 0.02 or more and 0.10 or less. Hereinafter, the ratio of the total area SP of the specific inorganic particles to the total area SR of the resin in the cross section of the specific resin composition is also referred to as the area ratio (SP / SR). The area ratio (SP / SR) is preferably 0.02 to 0.10, more preferably 0.03 to 0.08, and even more preferably 0.04 to 0.06.

[0036] By making the area ratio (SP / SR) equal to or greater than the lower limit, the dielectric constant of the carrier as a whole tends to be low, which is believed to improve the responsiveness to AC voltage and suppress the occurrence of density unevenness in images formed by a development method in which AC voltage is applied in a high-temperature, high-humidity environment. In addition, by having the area ratio (SP / SR) be equal to or less than the above upper limit value, the resin present in the internal voids of the magnetic particles reduces mechanical loads, making the magnetic particles less likely to crack, chip, etc., and is thought to suppress the occurrence of image unevenness resulting from these.

[0037] The area ratio (SP / SR) is determined by analyzing the cross sections of 100 particles of the specific resin composition contained in the internal voids of the magnetic particles in the same manner as in the above-mentioned method for confirming that the specific resin composition is disposed in the internal voids of the magnetic particles. Specifically, the total area of ​​the specific inorganic particle regions and the total area of ​​the resin regions in the 100 particles of the specific resin composition are determined to calculate the area ratio (SP / SR).

[0038] (resin) Examples of resins contained in the specific resin composition include styrene-acrylic acid copolymers; polyolefin resins such as polyethylene and polypropylene; polyvinyl or polyvinylidene resins such as polystyrene, (meth)acrylic resin, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; vinyl chloride-vinyl acetate copolymers; straight silicone resins or modified products thereof consisting of organosiloxane bonds; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyesters; polyurethanes; polycarbonates; amino resins such as urea-formaldehyde resins; and epoxy resins. In particular, the resin contained in the specific resin composition preferably contains a (meth)acrylic resin, from the viewpoint of increasing the affinity with the inorganic particles, thereby lowering the dielectric constant of the carrier and thereby suppressing concentration unevenness, and it is more preferable that the resin contains 50 mass% or more of the (meth)acrylic resin, based on the total mass of the resin in the specific resin composition, and it is particularly preferable that the resin contains 80 mass% or more of the (meth)acrylic resin, based on the total mass of the resin in the specific resin composition.

[0039] The specific resin composition preferably contains a (meth)acrylic resin having an alicyclic structure, from the viewpoint of lowering the dielectric constant of the carrier by increasing the affinity with inorganic particles, thereby suppressing uneven concentration. The (meth)acrylic resin having an alicyclic structure contains at least a polymerization component having an alicyclic structure as a polymerization component. Among the polymerization components of the (meth)acrylic resin having an alicyclic structure, the polymerization component having an alicyclic structure includes an alicyclic alkyl ester of (meth)acrylic acid (for example, an ester of (meth)acrylic acid and an alcohol having an alicyclic structure with a carbon number of 3 to 9), and specifically includes cyclohexyl (meth)acrylate. The (meth)acrylic resin having an alicyclic structure may be a copolymer of a polymerization component having an alicyclic structure and a polymerization component not having an alicyclic structure. As the polymerization component not having an alicyclic structure, a lower alkyl ester of (meth)acrylic acid (for example, a (meth)acrylic acid alkyl ester having an alkyl group with 1 to 9 carbon atoms) is preferable, and specific examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. These monomers may be used alone or in combination of two or more.

[0040] The (meth)acrylic resin having an alicyclic structure preferably contains cyclohexyl (meth)acrylate as a polymerization component. The content of the monomer unit derived from cyclohexyl (meth)acrylate contained in the (meth)acrylic resin having an alicyclic structure is preferably 75% by mass or more and 100% by mass or less, more preferably 85% by mass or more and 100% by mass or less, and even more preferably 95% by mass or more and 100% by mass or less, based on the total mass of the (meth)acrylic resin having an alicyclic structure.

[0041] From the viewpoint of suppressing uneven density, the resin contained in the specific resin composition preferably contains a resin having a nitrogen atom. It is considered that the specific resin composition contains a resin having a nitrogen atom, thereby improving the charge imparting property in a high-humidity environment, and suppressing the occurrence of uneven density of an image caused by low charge in a high-temperature and high-humidity environment.

[0042] Examples of the resin having a nitrogen atom include a (meth)acrylic resin having a nitrogen atom obtained by polymerizing dimethylaminoethyl (meth)acrylate, dimethylacrylamide, acrylonitrile, etc.; an amino resin such as urea, melamine, guanamine, aniline, etc.; an amide resin; a urethane resin; a copolymer of the above-mentioned resins; etc. Among these, the resin having a nitrogen atom is preferably a (meth)acrylic resin having a nitrogen atom, more preferably a (meth)acrylic resin having an amino group, and even more preferably a polymer containing dimethylaminoethyl (meth)acrylate as a polymerization component, from the viewpoint of further suppressing uneven density of an image.

[0043] When the resin contained in the specific resin composition contains a resin having a nitrogen atom, it is preferable to further contain a resin having no nitrogen atoms from the viewpoint of suppressing environmental differences in image density. By further containing a resin having no nitrogen atoms, it is possible to appropriately adsorb moisture, prevent an increase in charge especially under low humidity, and suppress environmental differences in image density.

[0044] Examples of the resin having no nitrogen atoms include those having no nitrogen atoms among the specific examples of resins described above. A (meth)acrylic resin having no nitrogen atoms is preferable, a (meth)acrylic resin having no nitrogen atoms and having an alicyclic structure is more preferable, and a polymer containing cyclohexyl (meth)acrylate as a polymerization component is even more preferable. When the specific resin composition contains both a resin having a nitrogen atom and a resin not having a nitrogen atom, the resin having a nitrogen atom is preferably contained in a range of 0.2 mass% or more and 5.0 mass% or less, and more preferably in a range of 0.3 mass% or more and 3.0 mass% or less, relative to the total mass of the resin in the specific resin composition.

[0045] From the viewpoint of adhesion to magnetic particles, the weight average molecular weight of the resin contained in the specific resin composition is preferably less than 300,000, more preferably less than 250,000, even more preferably 5,000 or more and less than 250,000, and particularly preferably 10,000 or more and 200,000 or less. Here, the weight average molecular weight is measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC was performed using a Tosoh GPC HLC-8120 as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight was calculated from the measurement results using a molecular weight calibration curve prepared with monodisperse polystyrene standard samples.

[0046] (Conductive particles) The specific resin composition may further contain conductive particles as other components in addition to the specific inorganic particles and the resin. The conductivity of the conductive particles is defined as a volume resistivity of 1×10 at 20° C. 7 This means that the resistance is less than Ω cm. However, it is preferable that the specific resin composition does not contain conductive particles, or that it contains conductive particles and the ratio of the total area of ​​the conductive particles to the total area of ​​the specific inorganic particles in the cross section of the specific resin composition is 0.005 or less. Hereinafter, the ratio of the total area SC of the conductive particles to the total area SP of the specific inorganic particles in the cross section of the specific resin composition is also referred to as the area ratio (SC / SP). The area ratio (SC / SP) is preferably 0 or more and 0.005 or less, more preferably 0 or more and 0.004 or less.

[0047] By making the area ratio (SC / SP) equal to or less than the upper limit, the amount of highly conductive components present in the internal voids of the magnetic particles is small, and the dielectric constant of the carrier as a whole tends to be low. This is believed to improve the responsiveness to AC voltage and suppress the occurrence of density unevenness in images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment. In addition, when the carrier of this embodiment has a resin coating layer described later, from the viewpoint of adjusting the resistance of the carrier while suppressing concentration unevenness, it is preferable that the resin coating layer contains conductive particles and that the area ratio (SC / SP) in the specific resin composition is within the above range.

[0048] Examples of the conductive particles include carbon black, as well as inorganic particles other than carbon black that have conductivity (for example, titanium oxide). The number average particle size of the conductive particles is, for example, in the range of 20 nm to 100 nm, preferably 30 nm to 80 nm, and more preferably 30 nm to 50 nm.

[0049] (Placement in internal cavity) As a method for disposing the specific resin composition in the internal voids of the magnetic particles, for example, a method using a resin liquid for disposing the specific resin composition in which the resin, the specific inorganic particles, and other components contained in the specific resin composition are dissolved or dispersed in a solvent can be mentioned.Specifically, for example, a method of mixing and stirring the resin liquid for disposing the specific resin composition and the magnetic particles having internal voids under a high temperature (for example, 75°C or higher and 95°C or lower) and reduced pressure (for example, -96kPa or higher and -81kPa in gauge pressure) environment can be mentioned. In addition, when the carrier has a resin coating layer described below, a resin liquid for forming a resin coating layer described below may be used as the resin liquid for disposing the specific resin composition, and the specific resin composition may be disposed in the internal voids while forming the resin coating layer.

[0050] <Resin coating layer> The carrier of the present embodiment may further have a resin coating layer that coats the magnetic particles having the specific resin composition disposed in the internal voids. The resin coating layer preferably contains the resin and the specific inorganic particles contained in the specific resin composition. The details of the resin and the specific inorganic particles contained in the resin coating layer are as described above. From the viewpoint of adequately penetrating the resin coating layer into the internal voids, the content of the specific inorganic particles contained in the resin coating layer is preferably 10% by mass or more and 60% by mass or less, more preferably 15% by mass or more and 55% by mass or less, and even more preferably 20% by mass or more and 50% by mass or less, relative to the total mass of the resin coating layer.

[0051] From the viewpoint of resistance control, the resin coating layer preferably contains the conductive particles described above. Details of the conductive particles contained in the resin coating layer are as described above. From the viewpoint of an appropriate resistance value, the content of the conductive particles contained in the resin coating layer is preferably 0.5 mass% or more and 15 mass% or less, more preferably 2 mass% or more and 10 mass% or less, and even more preferably 3 mass% or more and 8 mass% or less, relative to the total mass of the resin coating layer.

[0052] The resin coating layer may contain other components as necessary. Examples of other components include nitrogen-containing resin particles, inorganic particles other than the specific inorganic particles, and the like. The resin coating layer containing nitrogen-containing resin particles has the advantage of improving the charging speed. Examples of the nitrogen-containing resin particles include particles of (meth)acrylic resins obtained by polymerization of dimethylaminoethyl (meth)acrylate, dimethylacrylamide, acrylonitrile, etc.; amino resins such as urea, melamine, guanamine, aniline, etc.; amide resins; urethane resins; copolymers of the above resins; etc. When the resin coating layer contains nitrogen-containing resin particles, the content of the nitrogen-containing resin particles is preferably 5% by mass or more and 20% by mass or less, more preferably 8% by mass or more and 16% by mass or less, and even more preferably 9% by mass or more and 14% by mass or less, based on the total mass of the resin coating layer, from the viewpoints of improving the charging speed and the incorporation into the coating layer.

[0053] Examples of inorganic particles other than the specific inorganic particles include metal oxide particles such as titanium oxide (titania), barium titanate, magnesium titanate, calcium titanate, strontium titanate, iron oxide, copper oxide, zinc oxide, tin oxide, chromium oxide, cerium oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, and barium carbonate; metal compound particles such as barium sulfate, aluminum borate, and potassium titanate; and metal particles such as gold, silver, and copper. When the resin coating layer contains inorganic particles other than the specific inorganic particles, the content of the inorganic particles other than the specific inorganic particles is preferably 0.1% by mass or less with respect to the total mass of the resin coating layer from the viewpoint of reducing the relative dielectric constant of the entire carrier and suppressing uneven concentration.

[0054] From the viewpoint of resistance and electrostatic performance, the average thickness of the resin coating layer is preferably from 0.6 μm to 1.4 μm, more preferably from 0.8 μm to 1.2 μm, and particularly preferably from 0.8 μm to 1.1 μm. The average thickness of the resin coating layer is determined by analyzing the cross sections of 100 carriers in the same manner as the method for confirming the internal voids in the magnetic particles described above. Specifically, the thickness of the resin coating layer is determined at nine points on the cross section of each particle, and the average of all the thicknesses at each of the nine points for the 100 particles is taken as the average thickness of the resin coating layer.

[0055] Methods for forming a resin coating layer on the surface of magnetic particles include, for example, a wet method and a dry method. The wet method is a method that uses a solvent to dissolve or disperse the resin that constitutes the resin coating layer. On the other hand, the dry method is a method that does not use the above solvent.

[0056] Examples of wet manufacturing methods include an immersion method in which magnetic particles are immersed in a resin liquid for forming a resin coating layer to coat them, a spray method in which a resin liquid for forming a resin coating layer is sprayed onto the surfaces of magnetic particles, a fluidized bed method in which magnetic particles are fluidized in a fluidized bed and then sprayed with a resin liquid for forming a resin coating layer, and a kneader coater method in which magnetic particles are mixed with a resin liquid for forming a resin coating layer in a kneader coater and the solvent is removed. These manufacturing methods may be repeated or combined. The resin liquid for forming the resin coating layer used in the wet manufacturing method is prepared by dissolving or dispersing the resin, inorganic particles, and other components in a solvent. The solvent is not particularly limited, and examples of the solvent that can be used include aromatic hydrocarbons such as toluene and xylene, ketones such as acetone and methyl ethyl ketone, and ethers such as tetrahydrofuran and dioxane.

[0057] An example of the dry manufacturing method is a method in which a mixture of magnetic particles and a resin for forming a resin coating layer is heated in a dry state to form a resin coating layer. Specifically, for example, the magnetic particles and the resin for forming the resin coating layer are mixed in a gas phase and heated to melt, thereby forming a resin coating layer.

[0058] The formation of the resin coating layer may be carried out together with the step of disposing the specific resin composition in the internal voids of the magnetic particles, or may be carried out separately from the disposition of the specific resin composition. When the resin coating layer is formed separately from the disposition of the specific resin composition, for example, the resin coating layer is formed by the above method using magnetic particles in which the specific resin composition is disposed in the internal voids.

[0059] The exposed area ratio of the magnetic particles on the carrier surface is preferably 5% to 30%, more preferably 7% to 25%, and even more preferably 10% to 25%. The exposed area ratio of the magnetic particles on the carrier can be controlled by the amount of resin used to form the resin coating layer, and the greater the amount of resin relative to the amount of magnetic particles, the smaller the exposed area ratio.

[0060] The exposed area ratio of the magnetic particles on the carrier surface is a value determined by the following method. A target carrier and magnetic particles from which the resin coating layer has been removed from the target carrier are prepared. Methods for removing the resin coating layer from the carrier include, for example, a method for removing the resin coating layer by dissolving the resin component with an organic solvent, and a method for removing the resin coating layer by eliminating the resin component by heating at about 800°C. The carrier and magnetic particles are each used as measurement samples, and the Fe concentration (atomic%) on the sample surface is quantified by XPS, and the exposed area ratio (%) of the magnetic particles is calculated by (Fe concentration of the carrier)÷(Fe concentration of the magnetic particles)×100.

[0061] The number average particle diameter of the carrier is preferably 15 μm or more and 100 μm or less, more preferably 20 μm or more and 80 μm or less, and particularly preferably 25 μm or more and 40 μm or less, from the viewpoints of obtaining an appropriate adhesive force between the toner and the carrier, obtaining a sufficient amount of toner development, obtaining an appropriate magnetic brush, and forming an image with excellent fine line reproducibility. The number average particle diameter of the carrier is determined in the same manner as the number average particle diameter of the magnetic particles described above.

[0062] [Electrostatic image developer] The developer according to the present embodiment is a two-component developer containing the electrostatic image developing carrier according to the present embodiment and a toner. The toner contains toner particles and, if necessary, an external additive.

[0063] The mixture ratio (mass ratio) of the carrier to the toner in the developer is preferably from 100:1 to 100:30, more preferably from 100:3 to 100:20.

[0064] <Toner particles> The toner particles are configured to contain, for example, a binder resin, and, if necessary, a colorant, a release agent, and other additives.

[0065] -Binding resin- Examples of the binder resin include vinyl resins made of homopolymers of monomers such as styrenes (e.g., styrene, parachlorostyrene, α-methylstyrene, etc.), (meth)acrylic acid esters (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), and olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers. Examples of the binder resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosin, mixtures of these with the vinyl resins, and graft polymers obtained by polymerizing vinyl monomers in the coexistence of these. These binder resins may be used alone or in combination of two or more kinds.

[0066] The binder resin is preferably a polyester resin. The polyester resin may be, for example, a known amorphous polyester resin. The polyester resin may be used in combination with a crystalline polyester resin together with the amorphous polyester resin. However, the content of the crystalline polyester resin is preferably in the range of 2% by mass to 40% by mass (preferably 2% by mass to 20% by mass) based on the total binder resin.

[0067] The "crystallinity" of a resin refers to the presence of a clear endothermic peak rather than a stepwise change in the amount of endothermic heat in differential scanning calorimetry (DSC); specifically, it refers to the half-width of the endothermic peak being within 10°C when measured at a heating rate of 10 (°C / min). On the other hand, the term "amorphous" for a resin refers to a half-width exceeding 10° C., a stepwise change in endothermic heat quantity, or no clear endothermic peak being observed.

[0068] Amorphous polyester resin The amorphous polyester resin may be, for example, a condensation polymer of a polyvalent carboxylic acid and a polyhydric alcohol. As the amorphous polyester resin, a commercially available product or a synthesized product may be used.

[0069] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenylsuccinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). Among these, aromatic dicarboxylic acids are preferable as polyvalent carboxylic acids. The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, anhydrides thereof, and lower (e.g., carbon number 1 to 5) alkyl esters thereof. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0070] Examples of polyhydric alcohols include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, examples of polyhydric alcohols include aromatic diols and alicyclic diols, and more preferably aromatic diols. As the polyhydric alcohol, a polyhydric alcohol having a crosslinked or branched structure of three or more may be used in combination with the diol. Examples of the polyhydric alcohol having a trihydric or higher valence include glycerin, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0071] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C or higher and 80°C or lower, and more preferably 50°C or higher and 65°C or lower. The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), and more specifically, it is determined from the "extrapolated glass transition onset temperature" described in the method for determining glass transition temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0072] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less. The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less. The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less. The weight average molecular weight and number average molecular weight are measured by gel permeation chromatography (GPC). The molecular weight measurement by GPC is performed using a Tosoh GPC HLC-8120GPC as the measuring device, a Tosoh TSKgel SuperHM-M (15 cm) column, and THF solvent. The weight average molecular weight and number average molecular weight are calculated from the measurement results using a molecular weight calibration curve created with a monodisperse polystyrene standard sample.

[0073] The amorphous polyester resin can be obtained by a known production method, for example, by carrying out the reaction while removing water and alcohol generated during condensation by setting the polymerization temperature to 180° C. or higher and 230° C. or lower, and reducing the pressure in the reaction system as necessary. If the raw material monomer is not soluble or compatible at the reaction temperature, a high boiling point solvent may be added as a solubilizing agent to dissolve it. In this case, the polycondensation reaction is carried out while distilling off the solubilizing agent. If a monomer with poor compatibility is present in the copolymerization reaction, it is recommended that the monomer with poor compatibility is condensed in advance with the acid or alcohol to be polycondensed, and then polycondensed with the main component.

[0074] Crystalline polyester resin The crystalline polyester resin may be, for example, a polycondensate of a polyvalent carboxylic acid and a polyhydric alcohol. As the crystalline polyester resin, a commercially available product or a synthesized product may be used. Here, the crystalline polyester resin is preferably a polycondensate using a straight-chain aliphatic polymerizable monomer rather than a polymerizable monomer having an aromatic ring, since it easily forms a crystalline structure.

[0075] Examples of polyvalent carboxylic acids include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, and lower alkyl esters thereof (e.g., having 1 to 5 carbon atoms). The polyvalent carboxylic acid may be a trivalent or higher carboxylic acid having a crosslinked or branched structure in combination with a dicarboxylic acid. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, and their lower alkyl esters (e.g., carbon number 1 to 5). As the polyvalent carboxylic acid, a dicarboxylic acid having a sulfonic acid group and a dicarboxylic acid having an ethylenic double bond may be used in combination with these dicarboxylic acids. The polyvalent carboxylic acids may be used alone or in combination of two or more kinds.

[0076] Examples of polyhydric alcohols include aliphatic diols (for example, straight-chain aliphatic diols having 7 to 20 carbon atoms in the main chain). Examples of aliphatic diols include ethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosanedecanediol. Among these, 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol are preferred as aliphatic diols. The polyhydric alcohol may be a trihydric or higher alcohol having a crosslinked or branched structure in combination with the diol. Examples of the trihydric or higher alcohol include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol. The polyhydric alcohols may be used alone or in combination of two or more kinds.

[0077] Here, the polyhydric alcohol has an aliphatic diol content of 80 mol % or more, preferably 90 mol % or more.

[0078] The melting temperature of the crystalline polyester resin is preferably 50°C or higher and 100°C or lower, more preferably 55°C or higher and 90°C or lower, and even more preferably 60°C or higher and 85°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0079] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.

[0080] The crystalline polyester resin can be obtained, for example, by a known production method, like the amorphous polyester.

[0081] The content of the binder resin is preferably from 40% by mass to 95% by mass, more preferably from 50% by mass to 90% by mass, and even more preferably from 60% by mass to 85% by mass, based on the total mass of the toner particles.

[0082] -Coloring agent- Examples of colorants include carbon black, chrome yellow, Hansa Yellow, benzidine yellow, threne yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, Balkan orange, watch young red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont oil red, pyrazolone red, lithol red, rhodamine B lake, lake red C, pigment red, rose bengal, aniline blue, Examples of the dyes include pigments such as ultramarine blue, chalcoil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, and malachite green oxalate; and dyes such as acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, aniline black-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, and thiazole-based dyes. The colorant may be used alone or in combination of two or more kinds.

[0083] The colorant may be surface-treated as necessary, or may be used in combination with a dispersant. In addition, a plurality of types of colorants may be used in combination.

[0084] The content of the colorant is preferably from 1% by mass to 30% by mass, and more preferably from 3% by mass to 15% by mass, based on the total mass of the toner particles.

[0085] -Release agent- Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic or mineral / petroleum waxes such as montan wax, and ester waxes such as fatty acid esters and montan acid esters. The release agent is not limited to these.

[0086] The melting temperature of the release agent is preferably 50°C or higher and 110°C or lower, and more preferably 60°C or higher and 100°C or lower. The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) based on the "peak melting temperature" described in the method for determining melting temperature in JIS K7121:1987 "Method for measuring transition temperature of plastics."

[0087] The content of the release agent is preferably from 1% by mass to 20% by mass, and more preferably from 5% by mass to 15% by mass, based on the total mass of the toner particles.

[0088] -Other additives- Examples of other additives include known additives such as magnetic materials, charge control agents, inorganic powders, etc. These additives are contained in the toner particles as internal additives.

[0089] -Characteristics of toner particles, etc.- The toner particles may be toner particles having a single layer structure, or may be toner particles having a so-called core-shell structure composed of a core portion (core particle) and a coating layer (shell layer) that coats the core portion. The toner particles having a core-shell structure may be composed of, for example, a core containing a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer containing the binder resin.

[0090] The volume average particle size (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm. The volume average particle size (D50v) of the toner particles is measured using a Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte is measured using an ISOTON-II (manufactured by Beckman Coulter, Inc.). For the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and this is then added to 100 ml to 150 ml of the electrolyte. The electrolyte with the sample suspended in it is dispersed for 1 minute using an ultrasonic disperser, and the particle size distribution of particles with diameters in the range of 2 μm to 60 μm is measured using a Coulter Multisizer II with an aperture diameter of 100 μm. The number of particles sampled is 50,000. The particle size distribution based on volume is plotted from the smallest diameter side, and the particle size at which the cumulative 50% is reached is defined as the volume average particle size D50v.

[0091] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less. The average circularity of toner particles is calculated by (circular equivalent perimeter) / (perimeter) [(perimeter of a circle having the same projected area as the particle image) / (perimeter of the particle projected image)]. Specifically, it is a value measured by the following method. First, the toner particles to be measured are sucked and collected, flattened, and a still image of the particles is captured by instantaneous strobe light emission, and the particle image is analyzed by a flow-type particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation). The number of samples to be taken in order to calculate the average circularity is 3,500. When the toner contains an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant, and then ultrasonic treatment is performed to obtain toner particles from which the external additive has been removed.

[0092] -Method of manufacturing toner particles- The toner particles may be produced by any of a dry production method (e.g., a kneading and pulverizing method, etc.) and a wet production method (e.g., an aggregation and coalescence method, a suspension polymerization method, a dissolution suspension method, etc.). There is no particular limitation on these production methods, and any known production method may be used. Among these, it is preferable to obtain the toner particles by the aggregation and coalescence method.

[0093] Specifically, for example, when toner particles are produced by the aggregation and coalescence method, the toner particles are produced through a step of preparing a resin particle dispersion in which resin particles to be a binder resin are dispersed (resin particle dispersion preparation step), a step of aggregating resin particles (other particles, if necessary) in the resin particle dispersion (in a dispersion after mixing other particle dispersions, if necessary) to form aggregated particles (aggregated particle formation step), and a step of heating the aggregated particle dispersion in which the aggregated particles are dispersed, to fuse and coalesce the aggregated particles, thereby forming toner particles (fusion and coalescence step).

[0094] Each step will be described in detail below. In the following description, a method for obtaining toner particles containing a colorant and a release agent will be described, but the colorant and the release agent are used as necessary. Of course, additives other than the colorant and the release agent may be used.

[0095] -Resin particle dispersion preparation process- Along with a resin particle dispersion in which resin particles serving as a binder resin are dispersed, for example, a colorant particle dispersion in which colorant particles are dispersed, and a release agent particle dispersion in which release agent particles are dispersed are prepared.

[0096] The resin particle dispersion liquid is prepared, for example, by dispersing resin particles in a dispersion medium with the aid of a surfactant.

[0097] The dispersion medium used in the resin particle dispersion liquid is, for example, an aqueous medium. Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These may be used alone or in combination of two or more kinds.

[0098] Examples of the surfactant include anionic surfactants such as sulfate salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. Among these, anionic surfactants and cationic surfactants are particularly preferred. The nonionic surfactants may be used in combination with anionic surfactants or cationic surfactants. The surfactant may be used alone or in combination of two or more kinds.

[0099] In the resin particle dispersion, the resin particles are dispersed in the dispersion medium by a general dispersion method such as a rotary shear type homogenizer, a ball mill having a media, a sand mill, or a dyno mill. Depending on the type of resin particles, the resin particles may be dispersed in the dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method is a method in which the resin to be dispersed is dissolved in a hydrophobic organic solvent in which the resin is soluble, a base is added to the organic continuous phase (O phase) to neutralize it, and then an aqueous medium (W phase) is added to invert the phase from W / O to O / W, thereby dispersing the resin in the aqueous medium in the form of particles.

[0100] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably from 0.01 μm to 1 μm, more preferably from 0.08 μm to 0.8 μm, and even more preferably from 0.1 μm to 0.6 μm. The volume average particle size of the resin particles is measured by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (for example, LA-700 manufactured by Horiba, Ltd.), subtracting the cumulative distribution from the small particle size side for the volume of the divided particle size range (channel), and measuring the particle size at which the cumulative distribution is 50% of all particles as the volume average particle size D50v. The volume average particle sizes of particles in other dispersions are measured in the same manner.

[0101] The content of the resin particles in the resin particle dispersion is preferably from 5% by mass to 50% by mass, and more preferably from 10% by mass to 40% by mass.

[0102] In the same manner as the resin particle dispersion liquid, for example, a colorant particle dispersion liquid and a release agent particle dispersion liquid are also prepared. That is, the volume average particle size, dispersion medium, dispersion method, and particle content of the particles in the resin particle dispersion liquid are the same for the colorant particles dispersed in the colorant particle dispersion liquid and the release agent particles dispersed in the release agent particle dispersion liquid.

[0103] -Agglomerated particle formation process- Next, the resin particle dispersion liquid, the colorant particle dispersion liquid, and the release agent particle dispersion liquid are mixed together. Then, in the mixed dispersion, the resin particles, the colorant particles, and the release agent particles are hetero-aggregated to form aggregated particles containing the resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.

[0104] Specifically, for example, an aggregating agent is added to the mixed dispersion, the pH of the mixed dispersion is adjusted to be acidic (e.g., pH 2 or more and 5 or less), a dispersion stabilizer is added as necessary, and then the mixed dispersion is heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, glass transition temperature of the resin particles -30°C or more and glass transition temperature -10°C or less), and the particles dispersed in the mixed dispersion are aggregated to form aggregated particles. In the aggregated particle formation process, for example, the mixed dispersion may be stirred with a rotary shear homogenizer, an aggregating agent may be added at room temperature (e.g., 25°C), the pH of the mixed dispersion may be adjusted to an acidic state (e.g., pH 2 or more and 5 or less), a dispersion stabilizer may be added as necessary, and then the mixture may be heated.

[0105] Examples of the flocculant include a surfactant having a polarity opposite to that of the surfactant contained in the mixed dispersion, an inorganic metal salt, and a divalent or higher metal complex. When a metal complex is used as the flocculant, the amount of the surfactant used is reduced, and the charging characteristics are improved. If necessary, an additive that forms a complex or a similar bond with the metal ion of the flocculant may be used together with the flocculant. As this additive, a chelating agent is preferably used.

[0106] Examples of inorganic metal salts include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide. The chelating agent may be a water-soluble chelating agent, for example, oxycarboxylic acid such as tartaric acid, citric acid, gluconic acid, etc., aminocarboxylic acid such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), ethylenediaminetetraacetic acid (EDTA), etc. The amount of the chelating agent added is preferably from 0.01 to 5.0 parts by mass, and more preferably from 0.1 to less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.

[0107] -Fusion / coalescence process- Next, the aggregated particle dispersion liquid in which the aggregated particles are dispersed is heated, for example, to a temperature equal to or higher than the glass transition temperature of the resin particles (for example, a temperature 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to fuse and coalesce the aggregated particles to form toner particles.

[0108] Through the above steps, toner particles are obtained. After obtaining the aggregated particle dispersion in which the aggregated particles are dispersed, the aggregated particle dispersion and the resin particle dispersion in which the resin particles are dispersed are further mixed together to aggregate the aggregated particles so that the resin particles are further attached to the surfaces of the aggregated particles, thereby forming second aggregated particles; and the second aggregated particle dispersion in which the second aggregated particles are dispersed is heated to fuse and coalesce the second aggregated particles, thereby forming toner particles having a core-shell structure.

[0109] After the fusion and coalescence process is completed, the toner particles formed in the solution are subjected to a known washing process, solid-liquid separation process, and drying process to obtain dried toner particles. From the viewpoint of chargeability, the washing process is preferably performed by sufficient substitution washing with ion-exchanged water. From the viewpoint of productivity, the solid-liquid separation process is preferably performed by suction filtration, pressure filtration, etc. From the viewpoint of productivity, the drying process is preferably performed by freeze drying, air flow drying, fluidized drying, vibration type fluidized drying, etc.

[0110] The toner according to the present embodiment is produced, for example, by adding an external additive to the obtained toner particles in a dry state and mixing them. The mixing may be performed, for example, by using a V blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, if necessary, coarse particles of the toner may be removed using a vibration sieve, an air sieve, etc.

[0111] -External additives- Examples of the external additive include inorganic particles. Examples of the inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, and K2O·(TiO2). n , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.

[0112] The surface of the inorganic particles as an external additive may be subjected to a hydrophobic treatment. The hydrophobic treatment may be performed, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and examples thereof include silane coupling agents, silicone oils, titanate coupling agents, and aluminum coupling agents. These may be used alone or in combination of two or more. The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less with respect to 100 parts by mass of the inorganic particles.

[0113] Examples of external additives include resin particles (resin particles such as polystyrene, polymethyl methacrylate, and melamine resin), cleaning agents (for example, metal salts of higher fatty acids such as zinc stearate, and fluorine-based polymer particles), and the like.

[0114] The amount of the external additive is preferably from 0.01% by mass to 5% by mass, and more preferably from 0.01% by mass to 2.0% by mass, based on the toner particles.

[0115] <Image forming device, image forming method> The image forming apparatus according to the present embodiment includes an image carrier, a charging device for charging the surface of the image carrier, an electrostatic image forming device for forming an electrostatic image on the surface of the charged image carrier, a developing device for containing an electrostatic image developer and developing the electrostatic image formed on the surface of the image carrier as a toner image with the electrostatic image developer, a transfer device for transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing device for fixing the toner image transferred to the surface of the recording medium. The electrostatic image developer according to the present embodiment is used as the electrostatic image developer.

[0116] In the image forming apparatus according to this embodiment, an image forming method (the image forming method according to this embodiment) is carried out, which includes a charging step of charging the surface of an image carrier, an electrostatic image forming step of forming an electrostatic image on the surface of the charged image carrier, a developing step of developing the electrostatic image formed on the surface of the image carrier as a toner image using the electrostatic image developer according to this embodiment, a transfer step of transferring the toner image formed on the surface of the image carrier to the surface of a recording medium, and a fixing step of fixing the toner image transferred to the surface of the recording medium.

[0117] The image forming apparatus according to the present embodiment may be any of known image forming apparatuses, such as a direct transfer type apparatus in which a toner image formed on the surface of an image holder is directly transferred to a recording medium; an intermediate transfer type apparatus in which a toner image formed on the surface of an image holder is primarily transferred to the surface of an intermediate transfer body, and the toner image transferred to the surface of the intermediate transfer body is secondarily transferred to the surface of a recording medium; a cleaning device provided with a cleaning means for cleaning the surface of the image holder after the transfer of the toner image and before charging; and a static elimination device provided with a static elimination means for irradiating the surface of the image holder with static elimination light to eliminate static electricity after the transfer of the toner image and before charging. When the image forming apparatus according to the present embodiment is an intermediate transfer type apparatus, the transfer device is configured to have, for example, an intermediate transfer body to whose surface a toner image is transferred, a primary transfer device which primarily transfers the toner image formed on the surface of the image carrier onto the surface of the intermediate transfer body, and a secondary transfer device which secondarily transfers the toner image transferred onto the surface of the intermediate transfer body onto the surface of a recording medium.

[0118] In the image forming apparatus according to the present embodiment, for example, a portion including the developing device may have a cartridge structure (process cartridge) that is detachably attached to the image forming apparatus. As the process cartridge, for example, a process cartridge that contains the electrostatic charge image developer according to the present embodiment and is equipped with the developing device is preferably used.

[0119] An example of an image forming apparatus according to the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.

[0120] FIG. 2 is a schematic diagram showing the configuration of the image forming apparatus according to the present embodiment. The image forming apparatus shown in Fig. 2 includes first to fourth electrophotographic image forming units 10Y, 10M, 10C, and 10K (image forming means) that output images of the respective colors of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter sometimes simply referred to as "units") 10Y, 10M, 10C, and 10K are arranged in parallel at predetermined distances from each other in the horizontal direction. These units 10Y, 10M, 10C, and 10K may be process cartridges that are detachably attached to the image forming apparatus.

[0121] Above each of the units 10Y, 10M, 10C, and 10K, an intermediate transfer belt (one example of an intermediate transfer body) 20 is provided, which extends through each unit. The intermediate transfer belt 20 is provided wrapped around a drive roll 22 and a support roll 24, and runs in a direction from the first unit 10Y toward the fourth unit 10K. A force is applied to the support roll 24 by a spring (not shown) or the like in a direction away from the drive roll 22, and tension is applied to the intermediate transfer belt 20 wrapped around them. An intermediate transfer body cleaning device 30 is provided on the image carrier side of the intermediate transfer belt 20, facing the drive roll 22. The developing devices 4Y, 4M, 4C, and 4K of the units 10Y, 10M, 10C, and 10K are supplied with yellow, magenta, cyan, and black toners contained in toner cartridges 8Y, 8M, 8C, and 8K, respectively.

[0122] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration and operation, the first unit 10Y that forms a yellow image and is disposed upstream in the direction in which the intermediate transfer belt travels will be described here as a representative.

[0123] The first unit 10Y has a photoconductor 1Y that acts as an image carrier. Around the photoconductor 1Y, a charging roll (an example of a charging device) 2Y that charges the surface of the photoconductor 1Y to a predetermined potential, an exposure device (an example of an electrostatic image forming device) 3 that exposes the charged surface to a laser beam 3Y based on a color-separated image signal to form an electrostatic image, a developing device 4Y that supplies charged toner to the electrostatic image to develop it, a primary transfer roll 5Y (an example of a primary transfer device) that transfers the developed toner image onto an intermediate transfer belt 20, and a photoconductor cleaning device (an example of a cleaning device) 6Y that removes toner remaining on the surface of the photoconductor 1Y after the primary transfer are arranged in this order. The primary transfer roll 5Y is disposed inside the intermediate transfer belt 20, and is provided at a position facing the photoconductor 1Y. A bias power supply (not shown) that applies a primary transfer bias is connected to the primary transfer rolls 5Y, 5M, 5C, and 5K of each unit. Each bias power supply changes the value of the transfer bias applied to each primary transfer roll under the control of a control unit (not shown).

[0124] Hereinafter, the operation of forming a yellow image in the first unit 10Y will be described. First, prior to operation, the surface of the photoconductor 1Y is charged to a potential of −600V to −800V by the charging roll 2Y. The photoconductor 1Y has a conductivity (for example, a volume resistivity of 1×10 at 20° C. -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate having a resistivity of Ωcm or less. This photosensitive layer is usually highly resistive (the resistance of ordinary resins), but when irradiated with a laser beam, the resistivity of the portion irradiated with the laser beam changes. Therefore, the exposed surface of the charged photoreceptor 1Y is irradiated with a laser beam 3Y from the exposure device 3 in accordance with image data for yellow sent from a control unit (not shown). As a result, an electrostatic charge image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.

[0125] An electrostatic image is an image formed on the surface of the photoconductor 1Y by electrostatic charging. The laser beam 3Y reduces the resistivity of the irradiated parts of the photosensitive layer, causing the charged charges on the surface of the photoconductor 1Y to flow, while the charges remain in the parts not irradiated by the laser beam 3Y. This is a so-called negative latent image. The electrostatic image formed on the photoconductor 1Y rotates to a predetermined developing position as the photoconductor 1Y travels. At this developing position, the electrostatic image on the photoconductor 1Y is developed into a toner image by the developing device 4Y and made visible.

[0126] The developing device 4Y contains an electrostatic image developer including at least yellow toner and a carrier, for example. The yellow toner is triboelectrically charged by being stirred inside the developing device 4Y, and is held on a developer roll (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoconductor 1Y. As the surface of the photoconductor 1Y passes through the developing device 4Y, the yellow toner electrostatically adheres to the discharged latent image portion on the surface of the photoconductor 1Y, and the latent image is developed with the yellow toner. The photoconductor 1Y on which the yellow toner image has been formed continues to travel at a predetermined speed, and the toner image developed on the photoconductor 1Y is transported to a predetermined primary transfer position.

[0127] When the yellow toner image on the photoreceptor 1Y is transported to the primary transfer position, a primary transfer bias is applied to the primary transfer roll 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roll 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred onto the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control unit (not shown) in the first unit 10Y. On the other hand, the toner remaining on the photoconductor 1Y is removed and collected by the photoconductor cleaning device 6Y.

[0128] The primary transfer bias applied to the primary transfer rolls 5M, 5C, and 5K subsequent to the second unit 10M is also controlled in accordance with the first unit. In this manner, the intermediate transfer belt 20 onto which the yellow toner image has been transferred by the first unit 10Y is conveyed successively through the second to fourth units 10M, 10C, and 10K, where the toner images of each color are transferred and superimposed.

[0129] The intermediate transfer belt 20 onto which the four color toner images have been transferred in multiple layers through the first to fourth units reaches a secondary transfer section that is composed of the intermediate transfer belt 20, a support roll 24 that contacts the inner surface of the intermediate transfer belt, and a secondary transfer roll (an example of a secondary transfer device) 26 arranged on the image bearing surface side of the intermediate transfer belt 20. Meanwhile, a recording paper (an example of a recording medium) P is fed at a predetermined timing into the gap between the secondary transfer roll 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roll 24. The transfer bias applied at this time has a (-) polarity that is the same as the (-) polarity of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, and the toner image on the intermediate transfer belt 20 is transferred onto the recording paper P. The secondary transfer bias at this time is determined according to the resistance detected by a resistance detection means (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.

[0130] Thereafter, the recording paper P is sent to a pressure contact portion (nip portion) of a pair of fixing rolls in the fixing device 28, where the toner image is fixed onto the recording paper P, forming a fixed image.

[0131] The recording paper P onto which the toner image is transferred can be, for example, plain paper used in electrophotographic copying machines, printers, etc. In addition to the recording paper P, other examples of the recording medium include overhead projector sheets and the like. To further improve the smoothness of the image surface after fixing, it is preferable that the surface of the recording paper P is also smooth. For example, coated paper in which the surface of ordinary paper is coated with a resin or the like, art paper for printing, etc. are preferably used.

[0132] After the color image has been fixed, the recording paper P is conveyed toward the discharge section, and the series of color image forming operations is completed.

[0133] <Process cartridge> The process cartridge according to this embodiment is a process cartridge that contains the electrostatic image developer according to this embodiment and is equipped with a developing device that develops an electrostatic image formed on the surface of an image carrier using the electrostatic image developer into a toner image, and is detachable from an image forming apparatus.

[0134] The process cartridge according to this embodiment is not limited to the above configuration, and may be configured to include a developing device and, as necessary, at least one selected from other devices such as an image carrier, a charging device, an electrostatic image forming device, and a transfer device.

[0135] An example of a process cartridge according to the present embodiment will be described below, but the present invention is not limited to this example. In the following description, the main parts shown in the drawings will be described, and the description of the rest will be omitted.

[0136] FIG. 3 is a schematic diagram showing the process cartridge according to the present embodiment. The process cartridge 200 shown in FIG. 3 is configured, for example, by a housing 117 having a mounting rail 116 and an opening 118 for exposure, in which a photoconductor 107 (an example of an image carrier), a charging roll 108 (an example of a charging device) provided around the photoconductor 107, a developing device 111, and a photoconductor cleaning device 113 (an example of a cleaning device) are integrally combined and held together into a cartridge. In FIG. 3, reference numeral 109 denotes an exposure device (an example of an electrostatic image forming device), 112 denotes a transfer device, 115 denotes a fixing device, and 300 denotes a recording paper (an example of a recording medium). EXAMPLES

[0137] Hereinafter, the embodiments of the present invention will be described in detail with reference to examples, but the embodiments of the present invention are not limited to these examples. In the following description, unless otherwise specified, "parts" and "%" are based on mass.

[0138] [Preparation of ferrite particles] <Preparation of ferrite particles (1)> 1318 parts of Fe2O3, 587 parts of Mn(OH)2, and 96 parts of Mg(OH)2 were mixed and pre-fired at 900°C for 4 hours. The pre-fired product, 6.6 parts of polyvinyl alcohol, 0.5 parts of polycarboxylic acid as a dispersant, and zirconia beads with a media diameter of 1 mm were added to water, and the mixture was ground and mixed in a sand mill to obtain a dispersion. The volume average particle size of the particles in the dispersion was 1.5 μm. The dispersion liquid was used as a raw material, and granulated and dried using a spray dryer to obtain granules with a volume average particle size of 33 μm. Next, in an oxygen-nitrogen mixed atmosphere with an oxygen partial pressure of 1.2%, main sintering was performed using an electric furnace at a temperature of 1350°C for 4 hours, and then heating was performed in the air at a temperature of 850°C for 3 hours to obtain sintered particles. The sintered particles were crushed and classified to obtain ferrite particles (1) with a number average particle size of 30 μm. The obtained ferrite particles (1) had internal voids and had an internal porosity of 5%.

[0139] <Preparation of ferrite particles (6)> Ferrite particles (6) having a number average particle size of 30 μm were obtained in the same manner as for the ferrite particles (1), except that the oxygen partial pressure during main sintering was 1.4% and the temperature was 1250° C. The obtained ferrite particles (6) had internal voids and an internal porosity of 8%.

[0140] <Preparation of ferrite particles (16)> Ferrite particles (16) having a number average particle size of 30 μm were obtained in the same manner as for the ferrite particles (1), except that the oxygen partial pressure during main sintering was 1.6% and the temperature was 1150° C. The obtained ferrite particles (16) had internal voids and an internal porosity of 12%.

[0141] [Preparation of coating agent] The following coating agents (1) to (5) and (7) to (14) were prepared as a resin liquid that served both as a resin liquid for disposing the specific resin composition and as a resin liquid for forming a resin coating layer.

[0142] <Preparation of Coating Agent (1)> Resin (1): Cyclohexyl methacrylate polymer (weight average molecular weight: 350,000) 15.4 parts Resin (2): 2-(dimethylamino)ethyl methacrylate polymer (weight average molecular weight: 300,000) 0.39 parts Specific inorganic particles (1): Silica (number average particle size: 12 nm, fumed silica particles surface-treated with hexamethyldisilazane) 9.0 parts Conductive particles (1): Carbon black (number average particle size: 30 nm, manufactured by Cabot Corporation, product name: Vulcan XC72) 2.24 parts Nitrogen-containing resin particles: melamine resin particles (Eposter S (manufactured by Nippon Shokubai Co., Ltd.)) 3.0 parts Solvent: 150 parts toluene

[0143] The above materials and glass beads (diameter 1 mm, same amount as toluene) were charged into a sand mill and stirred at a rotation speed of 190 rpm for 30 minutes to obtain a coating agent (1).

[0144] <Preparation of Coating Agents (2) to (5)> Coating agents (2) to (5) were obtained in the same manner as in the preparation of coating agent (1), except that the amounts of specific inorganic particles (1) added were 14.4 parts, 5.4 parts, 18 parts, and 3.6 parts, respectively.

[0145] <Preparation of Coating Agents (7) to (10)> Coating agents (7) to (10) were obtained in the same manner as for coating agent (1), except that specific inorganic particles (7) to (10) were added in the amounts shown below instead of specific inorganic particles (1). Specific inorganic particles (7): Silica (number average particle size: 5 nm, fumed silica particles surface-treated with hexamethyldisilazane) 9.0 parts Specific inorganic particles (8): Silica (number average particle size: 90 nm, fumed silica particles surface-treated with hexamethyldisilazane) 9.0 parts Specific inorganic particles (9): 9.0 parts of alumina (number average particle size: 13 nm, alumina particles surface-treated with octylsilane) Specific inorganic particles (10): Calcium carbonate (number average particle size: 40 nm, calcium carbonate particles without hydrophobic treatment) 9.0 parts

[0146] <Preparation of Coating Agents (11) to (12)> Coating agents (11) to (12) were obtained in the same manner as for coating agents (1) and (7), respectively, except that the following conductive particles (11) were added in the following amounts instead of the conductive particles (1). Conductive particles (11): Carbon black (number average particle size: 55 nm, manufactured by Mitsubishi Chemical Corporation, product name: #3030B) 2.24 parts

[0147] <Preparation of Coating Agent (13)> Coating agent (13) was obtained in the same manner as coating agent (1), except that resin (2) was not added.

[0148] <Preparation of Coating Agent (14)> Coating agent (14) was obtained in the same manner as coating agent (1), except that specific inorganic particles (1) were not added.

[0149] [Creating the carrier] <Preparation of carrier (1)> 1000 parts of ferrite particles (1) and 180 parts of coating agent (1) were placed in a vacuum degassing kneader and stirred at 75°C and -20kPa (gauge pressure) for 2 hours, then heated to 85°C and distilled off toluene at a vacuum of -90kPa (gauge pressure) to form a carrier in which the ferrite particles were coated with resin. Subsequently, fine and coarse powders were removed with an elbow jet to obtain carrier (1). The average thickness of the resin coating layer in carrier (1) was 1.10 μm.

[0150] When the cross section of the obtained carrier (1) was examined, it was confirmed that a specific resin composition containing silica and resin was arranged in the internal voids of the ferrite particles (1). The area ratio (SP / SR) and the area ratio (SC / SP) in the specific resin composition were determined by the above-mentioned method and the results are shown in Table 1.

[0151] <Preparation of carriers (2) to (5) and (7) to (14)> Carriers (2) to (5) and (7) to (14) were obtained in the same manner as carrier (1), except that coating agents (2) to (5) and (7) to (14) were used instead of coating agent (1). The average thicknesses of the resin coating layers in carriers (2) to (5) and (7) to (14) were 1.26 μm, 0.99 μm, 1.36 μm, 0.93 μm, 1.10 μm, 1.10 μm, 1.00 μm, 1.05 μm, 1.1 μm, 1.1 μm, 1.09 μm, and 0.81 μm, respectively. When the cross sections of the obtained carriers (2) to (5) and (7) to (13) were examined, it was confirmed that the specific resin composition containing silica and resin was disposed in the internal voids of the ferrite particles (1). The area ratio (SP / SR) and area ratio (SC / SP) in the specific resin composition were determined by the above-mentioned method and the results are shown in Table 1. On the other hand, when the cross section of the carrier (14) was examined, it was confirmed that only resin was disposed in the internal voids of the ferrite particles (1).

[0152] <Preparation of carrier (6)> Carrier (6) was obtained in the same manner as carrier (1), except that ferrite particles (6) were used instead of ferrite particles (1). The average thickness of the resin coating layer in carrier (6) was 1.10 μm. When the cross section of the obtained carrier (6) was examined, it was confirmed that a specific resin composition containing silica and resin was disposed in the internal voids of the ferrite particles (6). The area ratio (SP / SR) and the area ratio (SC / SP) in the specific resin composition were determined by the above-mentioned method, and the results are shown in Table 1.

[0153] <Preparation of carrier (15)> 1000 parts of ferrite particles (1) and 180 parts of coating agent (1) were placed in a vacuum degassing kneader and stirred at 60°C and -20 kPa (gauge pressure) for 1 hour, then heated to 70°C and distilled off toluene at a vacuum of -75 kPa (gauge pressure) to form a carrier in which the ferrite particles were coated with resin. Subsequently, fine powder and coarse powder were removed using an elbow jet to obtain carrier (15). The average thickness of the resin coating layer in carrier (15) was 1.10 μm. When the cross section of the obtained carrier (15) was examined, it was confirmed that neither silica nor resin was disposed in the internal voids of the ferrite particles (1).

[0154] <Preparation of carrier (16)> Carrier (16) was obtained in the same manner as carrier (1), except that ferrite particles (16) were used instead of ferrite particles (1). The average thickness of the resin coating layer in carrier (16) was 1.10 μm. When the cross section of the obtained carrier (16) was examined, it was confirmed that a specific resin composition containing silica and resin was disposed in the internal voids of the ferrite particles (16). The area ratio (SP / SR) and the area ratio (SC / SP) in the specific resin composition were determined by the above-mentioned method, and the results are shown in Table 1.

[0155] [Preparation of developer] Any of the obtained carriers (1) to (16) and a toner obtained by the method described below were placed in a V blender in a mixing ratio of carrier:toner = 100:10 (mass ratio) and stirred for 20 minutes to obtain developers (1) to (16), respectively.

[0156] [evaluation] <Evaluation of density unevenness in solid images> A modified image forming apparatus Apeos C4030 (manufactured by Fujifilm Business Innovation Co., Ltd.) with a development method that applies an AC voltage was prepared, and the obtained developer was placed in the developing device. 50,000 test images (solid images) with 100% cyan image density were printed on A3 size paper under high temperature and high humidity conditions (35°C, 75% RH). For the 50,000th image (test image), nine points on the image area were measured with an image densitometer (X-Rite938, manufactured by X-Rite Co., Ltd.), and the standard deviation σ of the obtained density E was calculated and evaluated according to the following evaluation criteria.

[0157] -Evaluation criteria- A: The standard deviation σ of the density E of the test image is less than 0.05. B: The standard deviation σ of the density E of the test image is 0.05 or more and less than 0.07. B-: The standard deviation σ of the density E of the test image is 0.07 or more and less than 0.10. B--: The standard deviation σ of the density E of the test image is 0.10 or more and less than 0.13. C: The standard deviation σ of the density E of the test image is 0.13 or more and less than 0.18. D: The standard deviation σ of the density E of the test image is 0.18 or more.

[0158] [Table 1]

[0159] From the above results, it is understood that in this embodiment, density unevenness in an image formed by a development method in which an AC voltage is applied in a high temperature and high humidity environment is suppressed compared to the comparative example.

[0160] The abbreviations in the table are as follows: CHMA: Cyclohexyl methacrylate polymer ·DMAEMA: 2-(dimethylamino)ethyl methacrylate polymer Area ratio (SP / SR): The ratio of the total area SP of specific inorganic particles to the total area SR of resin in the cross section of a specific resin composition Area ratio (SC / SP): The ratio of the total area SC of conductive particles to the total area SP of specific inorganic particles in the cross section of a specific resin composition

[0161] [Toner production] The toner used in the preparation of the developer was obtained by the following method.

[0162] <Preparation of Resin Particle Dispersion (1)> Ethylene glycol (FUJIFILM Wako Pure Chemical Industries, Ltd.) 37 parts Neopentyl glycol (FUJIFILM Wako Pure Chemical Industries, Ltd.) 65 parts 1,9-nonanediol (FUJIFILM Wako Pure Chemical Industries, Ltd.) 32 parts Terephthalic acid (FUJIFILM Wako Pure Chemical Industries, Ltd.) 96 parts The above materials were charged in a flask, and the temperature was raised to 200°C over 1 hour. After confirming that the reaction system was stirred uniformly, 1.2 parts of dibutyltin oxide were added. The temperature was raised to 240°C over 6 hours while distilling off the water produced, and stirring was continued at 240°C for 4 hours to obtain a polyester resin (acid value 9.4 mgKOH / g, weight average molecular weight 13,000, glass transition temperature 62°C). This polyester resin was transferred in a molten state to an emulsifying and dispersing machine (Cavitron CD1010, Eurotech) at a rate of 100 g per minute. Separately, a dilute ammonia water with a concentration of 0.37%, which was obtained by diluting reagent ammonia water with ion-exchanged water, was placed in a tank, and the mixture was transferred to the emulsifying and dispersing machine at a rate of 0.1 liters per minute simultaneously with the polyester resin while being heated to 120°C with a heat exchanger. The emulsifying and dispersing machine was operated at a rotor rotation speed of 60Hz and a pressure of 5kg / cm. 2 By operating under the above conditions, a resin particle dispersion (1) having a volume average particle size of 160 nm and a solid content of 30% was obtained.

[0163] <Preparation of Resin Particle Dispersion (2)> Decanedioic acid (Tokyo Chemical Industry Co., Ltd.) 81 parts Hexanediol (FUJIFILM Wako Pure Chemical Industries, Ltd.) 47 parts The above materials were charged into a flask, and the temperature was raised to 160°C over 1 hour. After confirming that the reaction system was stirred uniformly, 0.03 parts of dibutyltin oxide was added. The temperature was raised to 200°C over 6 hours while distilling off the water produced, and stirring was continued at 200°C for 4 hours. The reaction liquid was then cooled, solid-liquid separation was performed, and the solid matter was dried at a temperature of 40°C under reduced pressure to obtain polyester resin (C1) (melting point 64°C, weight average molecular weight 15,000).

[0164] Polyester resin (C1) 50 parts Anionic surfactants (Neogen SC, Daiichi Kogyo Seiyaku Co., Ltd.) 2nd Division 200 parts deionized water The above materials were heated to 120°C and thoroughly dispersed using a homogenizer (Ultra Turrax T50, IKA Co., Ltd.), and then dispersed using a pressure discharge homogenizer. When the volume average particle size reached 180 nm, the particles were collected to obtain a resin particle dispersion (2) with a solid content of 20%.

[0165] <Preparation of Colorant Particle Dispersion (1)> Cyan pigment (Pigment Blue 15:3, Dainichi Seika Color & Chemicals Co., Ltd.) 10 parts Anionic surfactants (Neogen SC, Daiichi Kogyo Seiyaku Co., Ltd.) 2nd Division 80 parts deionized water The above materials were mixed and dispersed for 1 hour using a high-pressure impact disperser (Ultimaizer HJP30006, Sugino Machine Co., Ltd.) to obtain a colorant particle dispersion (1) having a volume average particle size of 180 nm and a solid content of 20%.

[0166] <Preparation of Release Agent Particle Dispersion (1)> Paraffin wax (HNP-9, Nippon Seiro Co., Ltd.) 50 parts Anionic surfactants (Neogen SC, Daiichi Kogyo Seiyaku Co., Ltd.) 2nd Division 200 parts deionized water The above materials were heated to 120°C and thoroughly dispersed using a homogenizer (Ultra Turrax T50, IKA), and then dispersed using a pressure discharge homogenizer. When the volume average particle size reached 200 nm, the particles were collected to obtain a release agent particle dispersion (1) with a solid content of 20%.

[0167] <Preparation of toner particles> ·Resin particle dispersion (1) 150 parts ·Resin particle dispersion (2) 50 parts Colorant particle dispersion (1) 25 parts Release agent particle dispersion (1) 35 parts 0.4 parts polyaluminum chloride 100 parts deionized water The above materials were put into a round stainless steel flask, thoroughly mixed and dispersed using a homogenizer (Ultra Turrax T50, IKA), and then heated to 48 ° C. in a heating oil bath while stirring the flask. After the reaction system was kept at 48 ° C. for 60 minutes, 70 parts of resin particle dispersion (1) were slowly added. Next, the pH was adjusted to 8.0 using a 0.5 mol / L aqueous sodium hydroxide solution, the flask was sealed, the seal of the stirring shaft was magnetically sealed, and the mixture was heated to 90 ° C. while continuing to stir and held for 30 minutes. Next, the mixture was cooled at a temperature drop rate of 5 ° C. / min, solid-liquid separation was performed, and the mixture was thoroughly washed with ion-exchanged water. Next, the solid-liquid separation was performed, and the mixture was redispersed in ion-exchanged water at 30 ° C., and stirred and washed for 15 minutes at a rotation speed of 300 rpm. This washing operation was repeated six more times, and when the pH of the filtrate reached 7.54 and the electrical conductivity reached 6.5 μS / cm, solid-liquid separation was performed, and vacuum drying was continued for 24 hours to obtain toner particles (1) having a volume average particle size of 5.7 μm.

[0168] <External Addition of Toner Particles> 100 parts of the above toner particles (1) and 0.7 parts of hydrophobic silica (RY50 manufactured by Nippon Aerosil Co., Ltd.) were mixed in a Henschel mixer to obtain a toner.

[0169] The present embodiment includes the following aspects. (((1))) Magnetic particles having internal voids; a resin composition that is disposed in at least a portion of the internal voids and contains inorganic particles including at least one selected from the group consisting of silica, alumina, and calcium carbonate, and a resin; A carrier for developing electrostatic images comprising: (((2))) The carrier for developing electrostatic images according to (((1))), wherein the internal porosity of the magnetic particles is 2% or more and 10% or less. (((3))) The electrostatic image developing carrier according to (((1))) or (((2))), wherein in a cross section of the resin composition, a ratio of a total area of ​​the inorganic particles to a total area of ​​the resin is 0.02 or more and 0.10 or less. (((4))) The electrostatic image developing carrier according to any one of (((1))) to (((3))), wherein the resin composition does not contain conductive particles, or contains the conductive particles and has a ratio of a total area of ​​the conductive particles to a total area of ​​the inorganic particles in a cross section of the resin composition of 0.005 or less. (((5))) The carrier for developing electrostatic images according to any one of (((1))) to (((4))), wherein the number average particle size of the inorganic particles is 5 nm or more and 90 nm or less. (((6))) The carrier for developing electrostatic images according to any one of (((1))) to (((5))), wherein the resin contains a resin having a nitrogen atom. (((7))) The electrostatic image developing carrier according to (((6))), wherein the resin further contains a resin having no nitrogen atoms. (((8))) a toner for developing an electrostatic image; A carrier for developing an electrostatic image according to any one of (((1))) to (((7))), 13. An electrostatic image developer comprising: (((9))) a developing device that contains the electrostatic image developer according to (((8))) and develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus. (((10))) An image carrier; a charging device for charging the surface of the image carrier; an electrostatic image forming device for forming an electrostatic image on the charged surface of the image carrier; a developing device that contains the electrostatic image developer according to (((8))) and develops the electrostatic image formed on the surface of the image carrier into a toner image by the electrostatic image developer; a transfer device for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing device for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising: (((11))) a charging step of charging the surface of the image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer according to (((8))); a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1,

[0170] According to the invention related to (((1))), there is provided a carrier for developing electrostatic images which suppresses uneven density in images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, compared to a case in which inorganic particles are not contained in the internal voids of magnetic particles. According to the invention related to (((2))), there is provided a carrier for developing electrostatic images which suppresses uneven density of images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, compared to when the internal porosity of the magnetic particles is less than 2% or exceeds 10%. According to the invention related to (((3))), there is provided a carrier for developing electrostatic images, which suppresses uneven density in images formed by a developing method in which an AC voltage is applied in a high-temperature and high-humidity environment, compared to when the ratio of the total area of ​​the inorganic particles to the total area of ​​the resin in the cross section of the resin composition is less than 0.02 or exceeds 0.10. According to the invention related to (((4))), there is provided a carrier for developing electrostatic images which suppresses uneven density in images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, as compared with a case in which the ratio of the total area of ​​the conductive particles to the total area of ​​the inorganic particles in the cross section of the resin composition exceeds 0.005. According to the invention related to (((5))), there is provided a carrier for developing electrostatic images which suppresses uneven density in images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, as compared with cases in which the number-average particle size of the inorganic particles is less than 5 nm or exceeds 90 nm. According to the invention related to (((6))), there is provided a carrier for developing electrostatic images which suppresses uneven density in images formed by a development method in which an AC voltage is applied in a high-temperature, high-humidity environment, compared to a case in which the resin does not contain a resin having a nitrogen atom. According to the invention related to (((7))), there is provided a carrier for developing electrostatic images in which the environmental difference in image density is suppressed, as compared with the case where the resin is a resin having a nitrogen atom. According to the invention related to (((8))), (((9))), (((10))), or (((11))), there is provided an electrostatic image developer, a process cartridge, an image forming apparatus, or an image forming method which suppresses uneven density in an image formed by a development method in which an AC voltage is applied in a high temperature and high humidity environment, compared to the case where an electrostatic image developing carrier is used that does not contain inorganic particles in the internal voids of magnetic particles. [Explanation of symbols]

[0171] 1Y, 1M, 1C, 1K Photoconductor (an example of an image carrier) 2Y, 2M, 2C, 2K Charging roll (example of charging device) 3 Exposure device (an example of an electrostatic image forming device) 3Y, 3M, 3C, 3K laser beam 4Y, 4M, 4C, 4K developing device 5Y, 5M, 5C, 5K Primary transfer roll (an example of a primary transfer device) 6Y, 6M, 6C, 6K Photoconductor cleaning device (example of cleaning device) 8Y, 8M, 8C, 8K toner cartridges 10Y, 10M, 10C, 10K Image forming units 20 Intermediate transfer belt (an example of an intermediate transfer body) 22 Driving Roll 24 Support roll 26 Secondary transfer roll (an example of a secondary transfer device) 28 Fixing device 30 Intermediate transfer body cleaning device P Recording paper (an example of a recording medium) 107 Photoconductor (an example of an image carrier) 108 Charging roll (an example of a charging device) 109 Exposure device (an example of an electrostatic image forming device) 111 Developing device 112 Transcription device 113 Photoconductor cleaning device (an example of a cleaning device) 115 Fixing device 116 Mounting Rail 117 Cabinet 118 Exposure Aperture 200 Process Cartridge 210 Cross section of magnetic particle 212 Circumscribing circle of a particle in a cross section 210 of the magnetic particle 214 Diameter of circumscribed circle 212 216 Center of circumscribed circle 212 218a, 218b: Points on the diameter 214 of the circumscribing circle 212 that are 1 / 2 the radius from the center 216 of the circumscribing circle 212 220 A square with points 218a and 218b as two opposite vertices 300 Recording paper (an example of a recording medium)

Claims

1. Magnetic particles having internal voids; a resin composition that is disposed in at least a portion of the internal voids and contains inorganic particles including at least one selected from the group consisting of silica, alumina, and calcium carbonate, and a resin; A carrier for developing electrostatic images comprising:

2. 2. The carrier for developing electrostatic images according to claim 1, wherein the internal porosity of said magnetic particles is from 2% to 10%.

3. 2. The carrier for developing an electrostatic image according to claim 1, wherein a ratio of a total area of ​​said inorganic particles to a total area of ​​said resin in a cross section of said resin composition is 0.02 or more and 0.10 or less.

4. 2. The carrier for developing an electrostatic image according to claim 1, wherein the resin composition does not contain conductive particles, or contains the conductive particles and has a ratio of a total area of ​​the conductive particles to a total area of ​​the inorganic particles in a cross section of the resin composition of 0.005 or less.

5. 2. The carrier for developing an electrostatic image according to claim 1, wherein the number average particle diameter of the inorganic particles is from 5 nm to 90 nm.

6. 2. The electrostatic image developing carrier according to claim 1, wherein the resin comprises a resin having a nitrogen atom.

7. 7. The electrostatic image developing carrier according to claim 6, wherein the resin further comprises a resin having no nitrogen atoms.

8. a toner for developing an electrostatic image; A carrier for developing an electrostatic image according to any one of claims 1 to 7, 13. An electrostatic image developer comprising:

9. a developing device that contains the electrostatic image developer according to claim 8 and develops an electrostatic image formed on a surface of an image carrier into a toner image by using the electrostatic image developer, A process cartridge that is detachably attached to an image forming apparatus.

10. An image carrier; a charging device for charging the surface of the image carrier; an electrostatic image forming device for forming an electrostatic image on the charged surface of the image carrier; a developing device that contains the electrostatic image developer according to claim 8 and develops the electrostatic image formed on the surface of the image carrier into a toner image by the electrostatic image developer; a transfer device for transferring the toner image formed on the surface of the image carrier to a surface of a recording medium; a fixing device for fixing the toner image transferred onto the surface of the recording medium; An image forming apparatus comprising:

11. a charging step of charging a surface of an image carrier; an electrostatic image forming step of forming an electrostatic image on the charged surface of the image carrier; a developing step of developing the electrostatic image formed on the surface of the image carrier into a toner image by using the electrostatic image developer according to claim 8; a transfer step of transferring the toner image formed on the surface of the image carrier onto a surface of a recording medium; a fixing step of fixing the toner image transferred onto the surface of the recording medium; The image forming method according to claim 1,

Citation Information

Patent Citations

  • Carrier core material, carrier for developing electrophotography using the same, and developer for electrophotography

    JP2019061188A

  • Electrostatic image developing carrier, electrostatic image developer, process cartridge, image forming device, and image forming method

    JP2021051216A